2001
DOI: 10.1016/s0893-133x(00)00191-3
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine and Behavioral Effects of Repetitive Transcranial Magnetic Stimulation in a Psychopathological Animal Model Are Suggestive of Antidepressant-like Effects

Abstract: The neuroendocrine and behavioral effects of repetitive transcranial magnetic stimulation (rTMS) were investigated in two rat

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
57
0
9

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 129 publications
(69 citation statements)
references
References 38 publications
(67 reference statements)
3
57
0
9
Order By: Relevance
“…The HAB and LAB rat lines, differing markedly in their inborn anxiety-related and acute stress coping behaviors (Liebsch et al 1998a,b;Keck et al 2001a), provide a promising tool for investigating the relationship between inborn emotionality, acute stress coping, physiological and neuroendocrine stress responses and their underlying mechanisms ). Thus, studies on aberrant patterns in these selected laboratory animals genetically predisposed to certain behavioral strategies may contribute to a better understanding of human psychopathology states.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The HAB and LAB rat lines, differing markedly in their inborn anxiety-related and acute stress coping behaviors (Liebsch et al 1998a,b;Keck et al 2001a), provide a promising tool for investigating the relationship between inborn emotionality, acute stress coping, physiological and neuroendocrine stress responses and their underlying mechanisms ). Thus, studies on aberrant patterns in these selected laboratory animals genetically predisposed to certain behavioral strategies may contribute to a better understanding of human psychopathology states.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, earlier studies showed a similar response of pituitary corticotropes to an i.v. CRH challenge in male HAB and LAB rats Keck et al 2001a).…”
Section: Aberrant Outcome Of the Combined Dex/crh Test In Male Hab Ratsmentioning
confidence: 98%
See 3 more Smart Citations